2023
DOI: 10.1080/0886022x.2023.2195012
|View full text |Cite
|
Sign up to set email alerts
|

Iron metabolism and chronic inflammation in IgA nephropathy

Abstract: IgA nephropathy (IgAN), an immune-mediated chronic inflammatory kidney disease, is the most common primary glomerular disease in Asia, especially in China and Japan. The pathogenesis of IgAN is complex, and the main cause of IgAN is explained by the ‘multiple hit’ theory, which states that the deposition of immune complexes in renal mesangial cells induces chronic inflammation that leads to kidney damage. Chronic inflammation is associated with iron metabolism, which also plays an essential role in the pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 209 publications
(165 reference statements)
0
6
0
Order By: Relevance
“…More and more studies have proven that iron is related to kidney disease; perhaps, iron can provide a potential strategy for treating kidney disease. Observational studies have recognized the associations between biomarkers of iron and several autoimmune diseases, such as systemic lupus erythematosus [62], adult Still's disease [63], and systemic juvenile rheumatoid arthritis [64], as well as IgAN [65]; however a causal relationship is yet to be defined. There is evidence from experimental and clinical studies that increased non-transferrin bound iron (NTBI) is a risk factor for the severity of AKI and poor clinical outcomes [66].…”
Section: Discussionmentioning
confidence: 99%
“…More and more studies have proven that iron is related to kidney disease; perhaps, iron can provide a potential strategy for treating kidney disease. Observational studies have recognized the associations between biomarkers of iron and several autoimmune diseases, such as systemic lupus erythematosus [62], adult Still's disease [63], and systemic juvenile rheumatoid arthritis [64], as well as IgAN [65]; however a causal relationship is yet to be defined. There is evidence from experimental and clinical studies that increased non-transferrin bound iron (NTBI) is a risk factor for the severity of AKI and poor clinical outcomes [66].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the relationship between ferroptosis and iron metabolism is mutually reinforcing and complementary. IgAN induces the dysregulation of iron metabolism, and disturbed iron homeostasis aggravates IgAN progression [ 266 , 267 ]. A recent study demonstrated that approximately 40% of IgAN patients presented with iron deposition in renal tissues [ 266 ].…”
Section: The Relationship Between Ferroptosis and Kidney Diseasementioning
confidence: 99%
“…TFR1 mediates iron homeostasis by regulating iron uptake through the endocytosis of iron-loaded TF. Urinary TF has been positively linked with endothelial cell hyperplasia, mesangial cell hyperplasia, tubular atrophy or interstitial fibrosis, according to the Oxford classification of IgAN patients [ 267 ]. Recent studies have suggested that TFR1 functions as a specific ferroptosis marker and plays an essential role in ferroptosis [ 268 ].…”
Section: The Relationship Between Ferroptosis and Kidney Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, tubular epithelial cell EVs loaded with functional cargoes such as chemokines, TGF-β1, CCL2 mRNA, and osteopontin transferred these cargoes to interstitial macrophages, aggravating kidney damage [ 145 ]. In kidney diseases such as IgA nephropathy [ 147 ] and diabetic kidney disease [ 148 ], increased inflammation leads to cellular oxidative damage. The spread of inflammation between tubules and renal interstitium may lead to significant kidney damage.…”
Section: Biology Of Extracellular Vesiclesmentioning
confidence: 99%